(untitled) (Theatrum historiae, 2013)
The study deals with the social rise and military career of a former cavalry messenger of the Luxembourg provincial council, Johann Beck (1588–1648), who gradually became a baron, the governor of Luxembourg and a field marshal as well as the owner of a lot of real estates both in his native duchy and in the Bohemian Kingdom. Attention is also paid to his military qualities and abilities, remarkable administrative and private building activities, fondness for religious orders and the descendants by whom his lineage died out.